2019
DOI: 10.3390/nu11030521
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders and the Gut Microbiota

Abstract: In recent years, there has been an emerging interest in the possible role of the gut microbiota as a co-factor in the development of autism spectrum disorders (ASDs), as many studies have highlighted the bidirectional communication between the gut and brain (the so-called “gut-brain axis”). Accumulating evidence has shown a link between alterations in the composition of the gut microbiota and both gastrointestinal and neurobehavioural symptoms in children with ASD. The aim of this narrative review was to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
203
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(230 citation statements)
references
References 191 publications
1
203
0
7
Order By: Relevance
“…The exact etiology is unknown: a combination of genetic and environmental risk factors, dysregulation of the immune system, inflammation and also maternal factors is proposed (Fattorusso et al, 2019). Increased systemic (Ashwood et al, 2011) and neuroinflammation (Vargas et al, 2005;Li et al, 2009) and even brain-specific autoantibodies (Vojdani et al, 2002;Silva et al, 2004;Connolly et al, 2006;Cabanlit et al, 2007;Wills et al, 2009), though not confirmed in another study (Todd et al, 1988), have been observed in ASD patients.…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 98%
See 1 more Smart Citation
“…The exact etiology is unknown: a combination of genetic and environmental risk factors, dysregulation of the immune system, inflammation and also maternal factors is proposed (Fattorusso et al, 2019). Increased systemic (Ashwood et al, 2011) and neuroinflammation (Vargas et al, 2005;Li et al, 2009) and even brain-specific autoantibodies (Vojdani et al, 2002;Silva et al, 2004;Connolly et al, 2006;Cabanlit et al, 2007;Wills et al, 2009), though not confirmed in another study (Todd et al, 1988), have been observed in ASD patients.…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 98%
“…Increased systemic (Ashwood et al, 2011) and neuroinflammation (Vargas et al, 2005;Li et al, 2009) and even brain-specific autoantibodies (Vojdani et al, 2002;Silva et al, 2004;Connolly et al, 2006;Cabanlit et al, 2007;Wills et al, 2009), though not confirmed in another study (Todd et al, 1988), have been observed in ASD patients. Hyperserotoninemia in ASD patients may also contribute to the etiology (Fattorusso et al, 2019).…”
Section: Neurological Disorders With Fmt Studies In Both Patients Andmentioning
confidence: 99%
“…and Candida albicans ( 8, 9 ). The dysbiosis of the ASD microbiome is believed to be associated with inflammation in intestinal epithelia and increased permeability of the gut-blood barrier ( 10 ). However, the mechanisms of how the intestinal microbiome affects ASD pathogenesis are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Undesired pro-inflammatory gastrointestinal side effects of anti-inflammatory treatments [70] have been discussed as a limitation of such therapies, which may also result in heterogeneity in treatment response. In light of the high prevalence of gastrointestinal disorders in children with ASD [71], finding therapies with little or no gastrointestinal adverse effects is of high importance. Vitamin D and omega-3 LCPUFA have been shown to positively affect gut microbial communities, mucosal homeostasis, and gut inflammation as well as systemic inflammation [29,31,72,73].…”
Section: Discussionmentioning
confidence: 99%